2011
DOI: 10.1037/a0021202
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial aid on Native American students.

Abstract: This paper examines how federal financial aid packages affect college persistence of Native Americans including packages with the Oklahoma's Promise grant. Using a state dataset that includes student-level data for the 2002-2006 time span in the state of Oklahoma, this study showed that motivated Native American women with income above $40,000 thrive in postsecondary education. In addition, students with financial aid packages that included the Oklahoma's Promise grant had the highest probability of retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
0
13
0
4
Order By: Relevance
“…The authors state that the impact of scholarships on college choice is true for both minoritized and low-income student groups, indicating that the scholarship likely increases college access for disadvantaged groups. In Oklahoma, Mendez et al (2011) found differences in college choices by background characteristics. Native American and African American low-income students were more likely to attend community college, whereas White students were more likely to attend research universities (Mendez et al, 2011).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The authors state that the impact of scholarships on college choice is true for both minoritized and low-income student groups, indicating that the scholarship likely increases college access for disadvantaged groups. In Oklahoma, Mendez et al (2011) found differences in college choices by background characteristics. Native American and African American low-income students were more likely to attend community college, whereas White students were more likely to attend research universities (Mendez et al, 2011).…”
Section: Resultsmentioning
confidence: 93%
“…Researchers also found that a state-wide scholarship positively influenced students’ college enrollment within the states of Massachusetts (Cohodes & Goodman, 2014), Tennessee (Ness & Tucker, 2008), and Oklahoma (Mendez, Mendoza, & Malcolm, 2011). In the Tennessee study, students were asked whether the scholarship affected their choice to attend college.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, heterogeneity bias occurs when researchers do not account for variations across groups. However, only until recently, researchers have begun to analyze differential effects of student aid packages by groups of students and type of financial aid package (Avery & Hoxby, 2004;Callender & Jackson, 2005;Kim, 2004;Mendez & Mendoza, 2008;Mendez, Mendoza, & Malcolm, 2011;Mendoza, Mendez, & Malcolm, 2009;Paulsen & St. John, 2002;Price, 2004). Moreover, Chen (2008) goes a step further, suggesting that research often takes limited consideration of the longitudinal characteristics of student departure and the possible time-varying effects of aid.…”
Section: Statistical Modelsmentioning
confidence: 99%